The evaluation of the truck and bus bias-tire business - Karan-u Panomyan; Naraporn Phaoprasert (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2020)
Until now, there are two main types of technology that could produce vehicle tires–bias tires and radial tires. The technology to produce bias tires had been around for decades, then the newer technology was launched to produce what was called the radial tires. As a result, although previously all vehicle used bias tires, now almost all passenger cars use radial tires. The bias tires are suitable only for vehicles that move on rough roads such as trucks and buses. This paper attempts to estimate the declining trend of the bias tire demand. Logarithm function was used to estimate the decline over a decade and the demand was forecasted using the moving average model, the exponential smoothing model, and the double exponential smoothing model. Moreover, SWOT analysis was performed to analyze the bias tires business. The results of this research clearly show that the bias tire demand for trucks and buses was declining rapidly within a couple years. Businesses that can still gain opportunity for the bias tires are the motorcycle tire business, the off-road tire business, and the agricultural vehicle tire business. Keywords: Bias tires, truck and bus business, decline trend estimation, SWOT analysis